2003
DOI: 10.1007/s10143-003-0253-1
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation, migration, and invasion of human glioma cells exposed to fractionated radiotherapy in vitro

Abstract: Radiotherapy is a well established treatment for malignant gliomas. This study describes the migration, proliferation, and invasion behaviour of two human glioma cell lines (GaMg and U-87 Mg) grown as multicellular tumour spheroids after radiotherapy. Migration and proliferation studies were performed using conventional and accelerated fractionation up to 60 Gy and 59.4 Gy, respectively. A dose-dependent growth and migratory response to irradiation independent of the type of fractionation was observed. A cocul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 26 publications
2
16
0
Order By: Relevance
“…In a recently published study, however, two human cell lines (GaMG and U-87MG) were irradiated up to 60 Gy. Their results indicate that irradiated malignant glioma subpopulations survive at this high absorbed dose, which is in agreement with our findings of a fraction of very radio-resistant cells (Gliemroth et al, 2003).…”
Section: Radiation Sterilisation Of Brain Tumour Cells C Bauréus-kochsupporting
confidence: 92%
“…In a recently published study, however, two human cell lines (GaMG and U-87MG) were irradiated up to 60 Gy. Their results indicate that irradiated malignant glioma subpopulations survive at this high absorbed dose, which is in agreement with our findings of a fraction of very radio-resistant cells (Gliemroth et al, 2003).…”
Section: Radiation Sterilisation Of Brain Tumour Cells C Bauréus-kochsupporting
confidence: 92%
“…In addition to their role in lowering cholesterol, the statin family of drugs has shown a broad range of functions including suppression of cancer cell growth in vitro and in vivo [9][10][11][12][13][14][15][16] in many cell types. Sur prisingly, the eVect of statins on ovarian cancer is limited to one study documenting lovastatin-induced growth inhibi tion [35].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed that statins inhibit certain can cer cell proliferation, invasion and migration in vitro and in vivo [9][10][11][12][13][14][15][16]. To determine the direct eVect of statins on ovarian cancer cells, we treated Hey 1B cells, a human ovarian carcinoma cell line, with lovastatin, a member of the statin family, at various doses for 48 h and the lova statin-induced Hey 1B cell death could be observed by a phase contrast microscope (Fig.1a).…”
Section: Statins Induce Apoptosis In Ovarian Cancer Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in some studies the invasiveness of cancer cells appears to be inhibited or unaffected by radiation. 14,15 Therefore, it is necessary to elucidate the effect of radiation on the invasion and metastatic potential of cancer cells, as well as the relevant molecular mechanisms involved. The better understanding of radiotherapy on cancer biology will certainly provide clues for intervention and improve the outcome of radiotherapy.…”
Section: Introductionmentioning
confidence: 99%